Holographic Mobile Applications for English Pronunciation Practice: A Study with Spanish-Speaking Children - Zainuddin; Lubis, Syahrul Efendi (Yayasan Insan Cipta Medan, 2025)
This study investigates the impact of a holographic mobile application on improving English pronunciation among Spanish-speaking children. Utilizing a quasi-experimental design, 60 students aged 8–10 were divided into experimental and control groups. The experimental group engaged with a holographic application that projected three-dimensional visualizations of mouth movements, while the control group received traditional pronunciation instruction. After an 8-week intervention, results showed that the experimental group achieved significantly higher gains in pronunciation accuracy, particularly with difficult English phonemes such as /θ/, /ð/, and /v/. Qualitative feedback revealed enhanced learner motivation, increased engagement, and reduced pronunciation anxiety among those using the holographic tool. These findings suggest that holographic mobile applications offer an effective, immersive alternative to conventional methods, especially in supporting young learners facing phonological challenges. The study highlights the potential for integrating emerging technologies into second language acquisition programs and recommends further research on long-term impacts and scalability across diverse learning contexts.